Comparison study of CC and CH vibration frequencies and eelectronic properties for mono, Di, Tri, and tetra-rings layer of arm chair (SWCNTs) - Al-Ani, Huda N. (Iraqi Journal of Physics, 2019)
Semi-empirical methods were applied for calculating the vibration frequencies and IR absorption intensities for normal coordinates of the mono (C56H28), di (C84H28), tri (C112H28) and tetra (C140H28) -rings layer for (7,7) armchair single wall carbon nanotube at their equilibrium geometries which were all found to have D7d symmetry point group. Assignment of the modes of vibration (3N-6) was done depending on the pictures of their modes by applying (Gaussian 03) program. Comparison of the vibration frequencies of (mono, di, tri and tetra) rings layer which are active in IR, and inactive in Ramman spectra. For C-H stretching vibrations, the results showed that vibration frequencies value increased with increased of length nano tube (rings layer SWCNT). The results include the relation for axial bonds, which are the vertical C-C bonds (annular bonds) in the rings and for circumferential bonds which are the outer ring bonds. Also include the assignment of puckering, breathing and clock-anticlockwise bending vibrations. They allow a comparative view of the charge density at the carbon atom too.